1983
DOI: 10.1002/aic.690290221
|View full text |Cite
|
Sign up to set email alerts
|

Four environment model of mixing and chemical reaction. Part I. Model development

Abstract: A new mathematical model (the four environment model) to describe turbulent R. V. MEHTA and J. M. TARBELL flow chemical reactors with complex reactions and separate reactant feed streams is developed. The feed stream residence time distributions, the batch chemical kinetics, and a single turbulent micromixing parameter, which may be estimated Department of Chemical Engineering from direct turbulence theory, are required as input information to the model. The and Center for Air Environment Studies model is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Mehta and Tarbell (1987) used Bourne's reaction in an unmixed feedstream multijet tubular reactor and observed that the concentration profiles (particularly the s profile) showed large deviations from the perfect mixing limit corresponding to a plug-flow reactor. Mechanistic models such as the three-environment model and four-environment model (Mehta and Tarbell, 1983) use data from these experiments to determine the value of the micromixing parameter for the models (Tarbell and Mehta, 1986). …”
Section: Aiche Journalmentioning
confidence: 99%
“…Mehta and Tarbell (1987) used Bourne's reaction in an unmixed feedstream multijet tubular reactor and observed that the concentration profiles (particularly the s profile) showed large deviations from the perfect mixing limit corresponding to a plug-flow reactor. Mechanistic models such as the three-environment model and four-environment model (Mehta and Tarbell, 1983) use data from these experiments to determine the value of the micromixing parameter for the models (Tarbell and Mehta, 1986). …”
Section: Aiche Journalmentioning
confidence: 99%
“…Environment models (Weinstein and Adler, 1967;Villermaux and Zoulalian, 1969;Mehta and Tarbell, 1983) represent imperfect mixing by a combination of environments, each in an extreme state of either perfect mixing or complete segregation. One or more free parameters control the amount of fluid entering each environment.…”
Section: Fluid-jbw Modelsmentioning
confidence: 99%
“…Other models in this same class include: the coalescence-redispersion model 1 (Curl, 1963); the interaction-by-exchange-with-the-mean (IEM) model (Villermaux and Devillon, 1972); and the four-environment model (Mehta and Tarbell, 1983).…”
Section: Mechanistic Modelsmentioning
confidence: 99%